2006
DOI: 10.1007/s10566-006-9013-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Child Protection Officers’ Decisions in Emergency Situations: An Experimental Study

Abstract: The present study examines the effects of demographic and personality variables on child protection workers' decisions in emergency situations. Four vignettes, describing emergency situations related to boys and girls, were randomly administered to 154 registered child protection workers by mail. The decision concerning the severity of the intervention was found to be associated with child's gender, worker's gender, and worker's authoritarianism. These results are discussed in light of the previous knowledge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…Although previous studies (Gammon, 2000;Lazar, 2006) found gender to be a professional characteristic that influenced decision outcomes, the current study did not produce this result. However, similar to past research findings (Gammon, 2000;Parada et al 2007), decision outcomes did differ based on the respondents' years of practice experience.…”
Section: Professional Characteristicscontrasting
confidence: 94%
See 1 more Smart Citation
“…Although previous studies (Gammon, 2000;Lazar, 2006) found gender to be a professional characteristic that influenced decision outcomes, the current study did not produce this result. However, similar to past research findings (Gammon, 2000;Parada et al 2007), decision outcomes did differ based on the respondents' years of practice experience.…”
Section: Professional Characteristicscontrasting
confidence: 94%
“…Gammon (2000) found no racial differences, but did conclude that professional characteristics influenced decision making in the study. Lazar's (2006) findings support the idea of professional characteristics being influential, specifically the gender and level of authoritarianism of the worker. One of Rossi and colleagues' (1999) conclusions was that case characteristics such as prior complaints were more influential in removal decisions than professional characteristics.…”
Section: Removal/placementsupporting
confidence: 73%
“…Lazar () discovered that social workers' assessment of the severity in cases involving child abuse were influenced by social workers with authoritative personality types as well as the gender of the child and the caseworker. Social workers with an authoritative personality deemed cases more serious and recommended more extensive child welfare intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The author argued that this speaks favourably to the use of validated risk instruments together with the judgement in assessing reports. Lazar (2006) (Stokes & Taylor, 2014).…”
Section: Significant Case Characteristicsmentioning
confidence: 99%
“…Recent research has emphasized that gender also plays a role in the inclination to use one's authority, particularly in emergency situations (Fargion 2006;Lazar 2006). Epistemologies and ontologies go hand in hand, and it could also be argued that personal style (personality and gendered identities) also play key parts in overall narratives of practice.…”
Section: Understanding Personal and Professional Identitiesmentioning
confidence: 99%